2021
DOI: 10.1111/1744-7917.12934
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic transcriptome analysis of Bombyx mori embryonic development

Abstract: Bombyx mori has been extensively studied but the gene expression control of its embryonic development is unclear. In this study, we performed transcriptome profiling of six stages of B. mori embryonic development using RNA sequencing (RNA‐seq). A total of 12 894 transcripts were obtained from the embryos. Of these, 12 456 transcripts were shared among the six stages, namely, fertilized egg, blastoderm, germ‐band, organogenesis, reversal period, and youth period stages. There were 111, 48, 41, 54, 77, and 107 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…The raw Illumina sequencing data from RNA‐seq conducted on embryos from 6 embryonic stages are deposited in the Sequence Read Archive with the accession number SRP292267 at the National Center for Biotechnology Information (Xu et al. , 2022a).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The raw Illumina sequencing data from RNA‐seq conducted on embryos from 6 embryonic stages are deposited in the Sequence Read Archive with the accession number SRP292267 at the National Center for Biotechnology Information (Xu et al. , 2022a).…”
Section: Methodsmentioning
confidence: 99%
“…RNA‐seq analysis has shown that in B. mori embryos, transcription factors are expressed throughout embryonic development (Xu et al. , 2022a). Therefore, multiple pathways regulate the accurate stage‐ or tissue‐specific expression of genes to ensure proper embryonic development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, the cellular genome does not change much during the lifetime of the organism, the cellular transcriptome is highly dynamic and depends on the state of the system. Several approaches for a wider range of systems at single and multi-cellular levels are already developed for dynamic transcriptome analysis [ [152] , [153] , [154] , [155] ], but by the nature of the analytical technology, these approaches are destructive and rely on quenching the systemic information at pre-fixed states.…”
Section: Glycolysis Monitoring Techniquesmentioning
confidence: 99%